2021
DOI: 10.3390/medicina57060613
|View full text |Cite
|
Sign up to set email alerts
|

Management Strategies for Brain Tumors Diagnosed during Pregnancy: A Case Report and Literature Review

Abstract: Background and Objectives: Maternal brain tumors diagnosed during pregnancy are very rare, and their clinical course remains incompletely understood. We recently experienced a case of a brain tumor diagnosed at 30 weeks of gestation, and the treatment was initiated after delivery at 32 weeks of gestation. In this study, we reviewed case reports of brain tumors diagnosed during pregnancy, focusing on whether the brain tumor was treated during pregnancy or after termination of pregnancy and on the timing of ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 25 publications
0
25
0
2
Order By: Relevance
“…The timing of a surgical resection of a brain tumor in pregnancy depends on the severity of neurological symptoms, the overall health and stability of the patient, the type of tumor and malignant potential, and the gestational age and viability of the fetus. For intracranial tumors identified in the third or late second trimesters, delivery of the baby at or after 34 weeks followed by initiation of treatment, including resection, has been associated with favorable maternal and fetal outcomes [11,12]. In stable patients, delivery may proceed vaginally [13], but for unstable patients needing urgent neurosurgical decompression, cesarean section may be recommended.…”
Section: Surgerymentioning
confidence: 99%
“…The timing of a surgical resection of a brain tumor in pregnancy depends on the severity of neurological symptoms, the overall health and stability of the patient, the type of tumor and malignant potential, and the gestational age and viability of the fetus. For intracranial tumors identified in the third or late second trimesters, delivery of the baby at or after 34 weeks followed by initiation of treatment, including resection, has been associated with favorable maternal and fetal outcomes [11,12]. In stable patients, delivery may proceed vaginally [13], but for unstable patients needing urgent neurosurgical decompression, cesarean section may be recommended.…”
Section: Surgerymentioning
confidence: 99%
“…Whereas infiltrative gliomas can be asymptomatic or present with seizures, higher-grade gliomas more commonly present with progressive symptoms of increased intracranial pressure. 16,17 These symptoms are most common in glioblastomas and should prompt brain imaging. In adults, standard treatment for glioblastoma has been maximal safe surgical resection followed by radiation and temozolomide chemotherapy.…”
Section: Key Pointsmentioning
confidence: 99%
“…Pregnancy is characterized by the production and regulation of various hormones and serum immune and growth factors as well as by vascular, hemodynamic, and structural body changes. 4,16 Multiple patient case series have reported that although pregnancy does not confer a higher risk for incidence of brain tumors, pregnancy is associated with worsening aggressive tumor behavior. 4,[12][13][14][15][16][17] Clarifying the impact of the full pregnancy state on brain tumor oncogenicity remains a challenge.…”
Section: Proposed Pregnancy Influences On Intracranial Tumorsmentioning
confidence: 99%
See 2 more Smart Citations